Foodomics : Advanced Mass Spectrometry in Modern Food Science and Nutrition. - Cifuentes, A. (New York : Wiley, 2013)
This book introduces the principles of foodomics through the review of advanced Mass Spectrometry (MS) technologies applied to this new discipline. The coverage details specific ""omics"" approaches based on MS technologies that have been (or can be) applied in foodomics, providing a picture of the most innovative applications and future trends. It explains the fundamental branches of foodomics such as metabolomics, proteomics, and systems biology. And it provides a global perspective on ""omics"" approaches based on MS techniques combined with systems biology in food science and nutrition, a.
5.5 CHANGES DURING FOOD STORAGE AND PROCESSING AND THEIR RELATIONSHIP TO QUALITY5.6 PROTEOMICS DATA INTEGRATION TO EXPLORE FOOD METABOLIC PATHWAYS AND PHYSIOLOGICAL ACTIVITY OF FOOD COMPONENTS; 5.7 NUTRIPROTEOMICS; 5.8 FINAL CONSIDERATIONS AND FUTURE TRENDS; REFERENCES; Chapter 6: Proteomics in Nutritional Systems Biology: Defining Health; 6.1 INTRODUCTION; 6.2 FROM FOOD PROTEINS TO NUTRIPROTEOMICS; 6.3 NUTRITIONAL PEPTIDE AND PROTEIN BIOACTIVES; 6.4 NUTRITIONAL PEPTIDE AND PROTEIN BIOMARKERS; 6.5 ECOSYSTEM-LEVEL UNDERSTANDING OF NUTRITIONAL HOST HEALTH; 6.6 CONCLUSIONS AND PERSPECTIVES.
REFERENCESChapter 7: MS-Based Methodologies for Transgenic Foods Development and Characterization; 7.1 INTRODUCTION; 7.2 CONTROVERSIAL SAFETY ASPECTS AND LEGISLATION ON GMOs; 7.3 ANALYSIS OF GMOs: TARGETED PROCEDURES AND PROFILING METHODOLOGIES; 7.4 CONCLUSIONS AND FUTURE OUTLOOK; 7.5 ACKNOWLEDGMENTS; REFERENCES; Chapter 8: MS-Based Methodologies to Study the Microbial Metabolome; 8.1 INTRODUCTION; 8.2 THE GUT MICROBIOTA AND THEIR ROLE IN METABOLISM; 8.3 METAGENOMICS; 8.4 METABOLOMICS; 8.5 MICROBIAL METABOLITES IN THE HUMAN GUT; 8.6 ANALYSIS OF THE MICROBIAL METABOLOME.
8.7 implications for human health and disease.
Print version record.
Keywords: Food -- Analysis; Mass spectrometry; Medical; TECHNOLOGY & ENGINEERING -- Food Science; Food -- Analysis; Mass spectrometry; Electronic books